2001
DOI: 10.1253/jcj.65.863
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ventricular Wall Thickening in Acute Myocarditis. A Serial Echocardiographic and Histopathologic Study.

Abstract: n the acute phase of myocarditis, 1-3 ventricular wall thickening is sometimes observed 4-18 and is believed to be caused by interstitial edema. However, no reports have characterized the wall thickening in a large number of cases and, furthermore, its cause is not yet fully understood. This prompted us to investigate whether ventricular wall thickening in the acute phase of myocarditis is attributable to interstitial edema, by focusing on the echocardiographic changes in left ventricular wall thickness and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 8 publications
1
24
0
1
Order By: Relevance
“…Furthermore, repetitive follow-up UCG examination may have revealed that the transient increase in IVSd was due to tissue edema, but not hypertrophy, as observed in acute myocarditis. [30][31][32][33] In spite of these limitations, the present study, which provides valuable information concerning early cardiac complications induced by cyclophosphamide, may contribute in the near future to an increase in the success rate for BSCT.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, repetitive follow-up UCG examination may have revealed that the transient increase in IVSd was due to tissue edema, but not hypertrophy, as observed in acute myocarditis. [30][31][32][33] In spite of these limitations, the present study, which provides valuable information concerning early cardiac complications induced by cyclophosphamide, may contribute in the near future to an increase in the success rate for BSCT.…”
Section: Discussionmentioning
confidence: 95%
“…The highest severity of edema is observed in the first three days of myocarditis and it undergoes gradual regression during the next eight days. Myocardial biopsies obtained after 30 days from the beginning of myocarditis do not show any characteristics of interstitial edema [3,4].…”
Section: Discussionmentioning
confidence: 90%
“…Hiramitsu et al, who on the basis of a careful histological analysis of biopsies demonstrated that myocardial cells do not undergo edema, also confirm this. The authors did not observe any changes of the longitudinal and transverse dimensions of the myocytes and emphasized that the edema is located only in the parenchymal cells [3]. The highest severity of edema is observed in the first three days of myocarditis and it undergoes gradual regression during the next eight days.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In patients with acute myocarditis, myocardial injury leads to transient interstitial edema, which induces thickening of the ventricular wall (1,2), occasionally also causing asymmetrical septal hypertrophy (ASH) and narrowing of the cavity of the left ventricle (LV), producing hypertrophic obstructive cardiomyopathy (HOCM) (3). Patients with acute myocarditis may also present with complete atrioventricular (AV) block.…”
Section: Introductionmentioning
confidence: 99%